A Prospective, Median 15-Year Comparison of Ponseti Casting and Surgical Treatment of Clubfoot. (3rd November 2021) - Recordon, James A.F.; Halanski, Matthew A.; Boocock, Mark G.; McNair, Peter J.; Stott, Ngaire S.; Crawford, Haemish A.
Abstract : Background: In 2010, 2 authors of this current study reported the results of Ponseti treatment compared with primary posteromedial release (PMR) for congenital talipes equinovarus in a cohort of 51 prospective patients. This current study shows outcomes recorded at a median of 15 years after the original treatment. Methods: Patient health records were available for all 51 patients at a median of 15 years (range, 13 to 17 years) following treatment of congenital talipes equinovarus with either the Ponseti method (25 patients [38 feet]) or PMR (26 patients [42 feet]). Thirty-eight of 51 patients could be contacted, and 33 patients (65%) participated in the clinical review, comprising patient-reported outcomes, clinical examination, 3-dimensional gait analysis, and plantar pressures. Results: Sixteen (42%) of 38 Ponseti-treated feet and 20 (48%) of 42 PMR-treated feet had undergone a further surgical procedure. The PMR-treated feet were more likely to undergo osteotomies and intra-articular surgical procedures (15 feet) than the Ponseti-treated feet (5 feet) (p < 0.05). Of the 33 patients reviewed with multimodal assessment, the Ponseti group, compared with the PMR group, demonstrated better Dimeglio scores (5.8 compared with 7.0 points; p < 0.05), Disease Specific Instrument (80.7 compared with 65.6 points; p < 0.05), Functional Disability Inventory (1.1 compared with 5.1; p < 0.05), and American Academy of Orthopaedic Surgeons (AAOS) Foot and Ankle Outcomes Questionnaire scores (52.2 compared with 46.6 points; p < 0.05), as well as improved total sagittal ankle range of motion in gait and ankle plantar flexion range at toe-off. The PMR group with clinical hindfoot varus displayed higher pressures in the lateral midfoot and the forefoot. Conclusions: Although the numbers of repeat surgical interventions following Ponseti treatment and primary PMR were similar, the PMR-treated feet had greater numbers of osteotomies and intra-articular surgical procedures. Functional outcomes were improved at a median of 15 years for feet treated with the Ponseti method compared with feet treated with PMR, with advantages seen in the Ponseti group over several domains. This study provides the most comprehensive evaluation of outcomes close to skeletal maturity in prospective cohorts, reinforcing the Ponseti method as the initial treatment of choice for idiopathic clubfeet. Level of Evidence: Therapeutic Level II . See Instructions for Authors for a complete description of levels of evidence.